PEMIKIRAN AHMAD DAHLAN TENTANG PENDIDIKAN ISLAM PADA MUHAMMADIYAH - Sung In kug (Universitas Muhammadiyah Tangerang, 2022)
AbstractThis article is about the thoughts of KH. Ahmad Dahlan on Islamic Education in Muhammadiyah. In this article, we discuss that Muhammadiyah is part of Indonesia's history that contributes as a carrier of modernity in Islam. In this article, the concept of Muhammadiyah education is explained, including bringing updates in the field of forming Islamic educational institutions which were originally a pesantren system into a school system and have included general lessons for religious schools or madrasas. For the Muhammadiyah education model, this article explains the integralistic model, adopts the substance and methodology of modern Dutch education into religious education madrasas, provides Islamic teaching content in modern Dutch public schools, and implements a cooperative system in the field of education. In the learning method, the emergence of the lecture method and the munadharah (dialogical) method in teaching created by Muslim scholars and with this method can be adjusted to the level of convenience of the subject matter, to suit the intellectual abilities of students. This research is a qualitative research with an emphasis on the comparative method process or comparing the thoughts of KH Ahmad Dahlan by conducting library research. The goals of Islamic education are a) general goals, cannot be achieved except after going through the process of teaching, appreciation, experience, and belief in the truth. b) the final goal, namely human beings who die and will face their God is the final goal of the Islamic education process. c) temporary goals are goals that will be achieved after students are given a certain number of experiences that have been planned in a formal education curriculum. d) operational goals are practical goals to be achieved by a certain number of educational activities that require certain abilities and skills which are more emphasized on the nature of appreciation and personality. K.H. Ahmad Dahlan carried out modernization in the field of Islamic education, from the cottage system which was only taught Islamic religious education lessons, from the cottage system which was only taught individually to class and supplemented with general knowledge lessons.